Factors Associated With Audience Participation in Local Radio Development Programmes in Negeri Sembilan, Malaysia - Zakariah, Adam Tanko (1993)
The objectives of the study were : (1) to investigate respondents' background in terms of their demographic and socioeconomic characteristics; (2) to identify the levels and kinds of audience participation in local radio development program mes; (3) to determine whether demographic, psychological and contemporary variables such as age, income, education, attitudes, perceptions, message contents, communication behaviour, source credibility, broadcast timing and involvement in voluntary associations have any relationship with audience participation in radio development programmes and ; (4) to identify the problems that hinder participation in radio development programmes. A total of 201 respondents from four village sin the state of Negeri Sembilan were selected using a multi -stage sampling method. Data were gathered through the interview method. Twelve hypotheses were tested using the Pearson-product.